Avaliação do potencial invasor do coral alcionáceo Stereonephthya aff.curvata(Nephtheidae-Alcyonacea) na Reserva Extrativista Marinha de Arraial do Cabo (RJ) - Lages, Bruno Gualberto (2003)
Corals produce a large variety of secondary metabolites which can have a range of ecological significances in the marine environment. The species of soft coral Stereonephthya aff. curvata from Pacific Ocean is abundant in the Marine Reserve of Arraial do Cabo. This work evaluated the invading potential of this exotic coral through the stuffy of the action of secondary metabolites of this species as allelopathic and defense agents. We tested in the field assays the crude extracts (hexane; dichloromethane; ethil acetate; methanol) from this species and no-polar extract (hexane) and the main fraction made an efficient defense against generalist fishes. Otherwise, Allelopathic action was evaluated in space competition and it caused contact necrosis in the endemic gorgonian Phyllogorgia dilatata. Both strategies, of expansion and/or perpetuation, characterized an expressive invasor potential for Stereonephthya aff. curvata, and indicate that it is a real threat to the biological integrity of the Marine Extractive Reserve of the Arraial do Cabo, RJ.